2013
DOI: 10.5799/ahinjs.02.2013.03.0094
|View full text |Cite
|
Sign up to set email alerts
|

Seroprevalence and risk factors for cytomegalovirus infection among pregnant women in southern Nigeria

Abstract: Objective: Vertically transmitted cytomegalovirus (CMV) is the most common cause of preventable congenital infection, including deafness and intellectual impairment worldwide. Till date, there is no consensus on routine antenatal screening worldwide. The objective of this study was to determine the prevalence of previous and primary CMV infection among antenatal women at the University of Benin Teaching Hospital (UBTH) and the effect of age, socioeconomic class, parity and gestational age on prevalence. Method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
5
8
0
Order By: Relevance
“…This is in agreement with studies in other region; 4 % in Nigeria [41], 8.1 % in Kenya [19], 6 % in Sudan [40]. However, our finding is in contrast with other studies in similar setting [39] and 2.5 % in Iran [43], 1.7 % in Korea [44].…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…This is in agreement with studies in other region; 4 % in Nigeria [41], 8.1 % in Kenya [19], 6 % in Sudan [40]. However, our finding is in contrast with other studies in similar setting [39] and 2.5 % in Iran [43], 1.7 % in Korea [44].…”
Section: Discussionsupporting
confidence: 91%
“…In this study the maternal prevalence of anti-CMV IgG was 95.5 %, which is comparable with other research findings in a similar setting [39] and different studies in developing countries such as; 77.3 % in Kenya [19], 97.5 % in Sudan [40], 96 % in Egypt [21], 92 % in Nigeria [41], and 87 % in Gambia [42]. …”
Section: Discussionsupporting
confidence: 90%
“…In a study on CMV prevalence, the highest number of respondents, attending antenatal clinics in their centre was that of younger pregnant women [2,19]. This is similar to our finding and can be explained by the fact that the studies were done in the same geographic region with similar socio-cultural practices and religious believe.…”
Section: Discussionsupporting
confidence: 88%
“…The high prevalence of 94.3% for CMV IgG in our study is also worrisome, and this is the case with many of the studies from the region [19,21].…”
Section: Discussionsupporting
confidence: 57%
“…On the other hand, our result showed a high CMV IgG seropositivity of 94.6% in multiparous women. However, high parity also has been implicated as associated risk factor for CMV infection, and previous studies suggested a positive correlation of congenital CMV with a household size, overcrowding, and low socioeconomic status [23].This high seroprevalence rate among multiparous women could be related to the unhygienic practices in large sized family and direct contact with infected children [29].…”
Section: Discussionmentioning
confidence: 97%